The Influence of Psychological Dimensions in the Language of Female Poets: An Analysis Study of Al-Khansa's Literary Works - Tahliyatud Dayyanah,; Mu'adzah, Maryam; Wildana Wargadinata, (Shaut al Arabiyyah, 2023)
Poems that contain excessive expressions of grief with words that are heartbreaking are called ritsa' or lamentations, this style of poetry dominates in Al Khansa's poetry. The psychological dimension can affect the theme, choice of words, and style of language. The purpose of this study is to analyze the forms of literary language used by Al Khansa and the background of his life which made Al Khansa immortalize the events he experienced in his poems. The method used in this study is descriptive qualitative with a historical approach that takes data from the history of the poet Al Khansa. The stages of the research started from the selection of topics and problem formulation, data accumulation, data analysis, data interpretation, and finally drawing conclusions. The results of this study are: (1) The forms of poetic language chosen by Al Khansa are words that show sadness, lamentation, and revenge. (2) The background of Al Khansa in his literary work is the death of his two brothers in the war which affected his soul and inner state in creating his poetry. The lamentations of grief from the families left behind by the death of two of their brothers in the war are contained in poetry. The conclusion of this study shows that the model of writing literary works is influenced by the internal dimensions of the creator, including the psychological conditions experienced by writers.